Low expression of tRF‐Pro‐CGG predicts poor prognosis in pancreatic ductal adenocarcinoma. Issue 5 (6th March 2021) - Li, Jun; Jin, Lei; Gao, Yuan; Gao, Peng; Ma, Le; Zhu, Bei; Yin, Xu; Sui, Shizhen; Chen, Shuai; Jiang, Zijian; Zhu, Chunfu
ABSTRACT: Background & Aims: tRFs (tRNA‐derived RNA fragments) have been reported to facilitate cancer progression in multiple cancers. However, their role in pancreatic ductal adenocarcinoma (PDAC) remains to be determined. In this study, we mainly investigated the expression of tRF‐Pro‐CGG in pancreatic ductal adenocarcinoma and evaluated its relationship with the clinicopathology and survival time of patients. Methods: 37 cases of pancreatic ductal adenocarcinoma, and 15 cases of normal pancreatic tissues were collected which were resected by surgery from January 2017 to June 2020 from the Department of Hepatobiliary and Pancreatic surgery of Changzhou second people's Hospital. The expression of tRF‐Pro‐CGG in paraffin‐embedded tissues was detected by fluorescence in situ hybridization (FISH). The clinical data including age, sex, tumor location, tumor diameter, tumor clinical stage (TNM stage), depth of invasion, regional lymph node metastasis, serum CA199, and serum CEA were collected and analyzed retrospectively, whether the expression tRF‐Pro‐CGG was correlation with the pathological parameters and clinical outcomes of patients. Results: The expression level of tRF‐Pro‐CGG was significantly downregulated in PDAC and associated with an advanced TNM stage (P=0.000) and the N stage (P=0.000) of patients. More importantly, low tRF‐Pro‐CGG expression predicted poor survival in PDAC patients (P=0.003). Conclusions: TRF‐Pro‐CGG is under‐expressed in PDAC and is associated with short clinical survival and poor prognosis. tRF‐Pro‐CGG is an independent prognostic factor, which highlights its role as a potential biomarker for PDAC progression and therapy. Abstract : Expression of tRF‐Pro‐CGG in pancreatic ductal adenocarcinoma and its clinical significance: Low expression of tRF‐Pro‐CGG predicts poor prognosis in pancreatic ductal adenocarcinoma. The expression of tRF‐Pro‐CGG has certain value in the diagnosis of PDAC patients.